2014
DOI: 10.2135/cropsci2013.09.0596
|View full text |Cite
|
Sign up to set email alerts
|

Broccoli Cultivar Performance under Organic and Conventional Management Systems and Implications for Crop Improvement

Abstract: To determine if present commercial broccoli cultivars meet the diverse needs of organic management systems, such as adaptation to low N input, mechanical weed management, and no chemical pesticide use, and to propose the selection environments for crop improvement for organic production, we compared horticultural trait performance of 23 broccoli cultivars (G) under two management (M) systems (organic and conventional) in two regions of the United States (Oregon and Maine), including spring and fall trials. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…However, often, the N availability in the year of application is less than 100 kg N ha −1 which leads to yield reduction of N demanding crops such as potato and cabbage (Finckh et al 2006;Tiemens-Hulscher et al 2014). Renaud et al (2014) concluded from various trials comparing a set of 23 broccoli cultivars for their performance under conventional and organic conditions that overall the rankings of cultivars were similar (with exceptions) but that not all high-yielding genotypes were good performers with respect to yield stability across years and locations and were not very tolerant to N stress conditions, for example occurring in cold spring conditions. Organic crop management is not only characterized by specific ways of nitrogen husbandry but also by disease management; the latter can also affect the NUE of cultivars.…”
Section: Do Crop Traits Contributing To Nitrogen Use Efficiency Diffementioning
confidence: 99%
“…However, often, the N availability in the year of application is less than 100 kg N ha −1 which leads to yield reduction of N demanding crops such as potato and cabbage (Finckh et al 2006;Tiemens-Hulscher et al 2014). Renaud et al (2014) concluded from various trials comparing a set of 23 broccoli cultivars for their performance under conventional and organic conditions that overall the rankings of cultivars were similar (with exceptions) but that not all high-yielding genotypes were good performers with respect to yield stability across years and locations and were not very tolerant to N stress conditions, for example occurring in cold spring conditions. Organic crop management is not only characterized by specific ways of nitrogen husbandry but also by disease management; the latter can also affect the NUE of cultivars.…”
Section: Do Crop Traits Contributing To Nitrogen Use Efficiency Diffementioning
confidence: 99%
“…However, crop varieties bred in the location of intended use have been shown to be better performers than varieties bred outside of the intended region (Annicchiarico et al, 2012). Most breeding programs are also conducted using conventional farming practices though cultivars developed in these systems are not always the best performing ones in organic farming systems (Burger et al, 2008;Reid et al, 2011;Renaud et al, 2014a). In a large tomato germplasm screening trial conducted under organic management at three locations in Europe, Horneburg and Becker (2008) found that out of 3500 accessions, >71% of the most successful entries came from colleagues within the organic horticulture industry.…”
mentioning
confidence: 99%
“…Low-input organic production systems also tend to be highly heterogeneous as a result of the wide range of soil and fertility management practices employed. Greater heterogeneity in organic systems supports the idea that direct selection would lead to varieties that are better adapted to organic systems, rather than indirect selection in high-input conventional systems (Reid et al, 2011;Renaud et al, 2014a). Trialing will need to occur under a wide range of conditions that characterize the breadth of organic farms, which is why participatory breeding has been successfully used to develop new potato, cabbage, cauliflower, and sweet corn cultivars optimally adapted to these systems (Almekinders et al, 2014;Chable et al, 2008;Shelton, 2014).…”
mentioning
confidence: 99%
“…Particularly for cauliflower crops, adaptability varies widely according to cultivar and edaphoclimatic conditions (Morais Jr et al, 2012); thus, the study of more competitive genotypes adapted to a particular region may also complement weed control (Colquhoun et al, 2017;Cavalieri et al, 2018). Another aspect to be considered is that different cultivars of a particular vegetable may have different levels of adaptability to the same production system (Meagy et al, 2013;Renaud et al, 2014;Resende et al, 2016), and one should evaluate the viability of Brachiaria as a mulch option for cauliflower cultivation, as well as the adaptability of commercial cultivars in this cultivation system. Previous studies have shown that vegetables differ in their response to mulching (Resende et al, 2005;Santos et al, 2011;Ferreira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the evaluation of cultivars in environments with low use of chemical inputs allows the selection of more appropriate materials for a production system (Renaud et al, 2014), e.g., mulch without herbicides.…”
Section: Introductionmentioning
confidence: 99%